THE PRACTICE OF NOBLE VALUES AMONG PRIMARY SCHOOL STUDENTS IN MALAYSIA - Mohd Yusoff, Mohd Zailani; Haji Othman, Mohamad Khairi; Suhid, Asmawati; Khalid, Rozalina (Jurnal Ilmiah Peuradeun, 2019)
Social problems among students have become very serious in recent years. Therefore, the issues that need to be addressed are the practices that exist among them. This study will share a research finding that identifies the level of practice of applying noble values among primary school children. This study used qualitative research designs through interviews and observations and quantitative survey studies where data were collected through questionnaires involving 321 primary school children from four primary schools in the North Zone of Peninsular Malaysia. Overall, the findings show that the practice of noble values is admirable. This study found that there was a significant difference in values of noble practices in terms of school types. In addition, the findings also found that values of respect are the most dominant values practiced by primary school students followed by other values.